A rhizomatic learning process to create collective knowledge in entrepreneurship education: Open innovation and collaboration beyond boundaries. Issue 2 (April 2017) - Bissola, Rita; Imperatori, Barbara; Biffi, Alfredo
Entrepreneurship literature has proven the efficacy of an experiential and collaborative learning approach that promotes entrepreneurial capabilities, that is, risk-taking, positive thinking, vision, intuitive decision-making, creative problem-solving, managing interdependency, tolerating ambiguity and innovation. To advance this, we propose a Deleuzian-inspired theoretical framework for entrepreneurship learning around innovation based on a rhizomatic perspective. We offer an illustrative case and identify the advantages and challenges of a rhizomatic approach to learning.